2011
DOI: 10.1111/j.1533-2500.2011.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Costs in Patients with Painful Diabetic Peripheral Neuropathy Prescribed Pregabalin or Duloxetine

Abstract: No differences were noted in all-cause costs attributable to pregabalin or duloxetine. Although patients receiving pregabalin had a significantly greater pre- to post-index increase in pDPN-related health care costs compared with patients receiving duloxetine, this may have been due to an imbalance in patient exclusion criteria between cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 24 publications
2
15
0
2
Order By: Relevance
“…Some studies have analyzed health-care costs in patients with PDPN treated with pregabalin, duloxetine, or other usually used drugs. In general, all show similar results, with a good cost-effective profile for both drugs 132134…”
Section: Pharmacological Therapeutic Modalities For Diabetic Neuropatsupporting
confidence: 53%
“…Some studies have analyzed health-care costs in patients with PDPN treated with pregabalin, duloxetine, or other usually used drugs. In general, all show similar results, with a good cost-effective profile for both drugs 132134…”
Section: Pharmacological Therapeutic Modalities For Diabetic Neuropatsupporting
confidence: 53%
“…Costs due to early retirement were not included in the calculations; however, data from 2012 show that back pain (and other musculoskeletal disorders) is the reason for only approximately 12% of the cases of early retirement nowadays [5]. Even higher costs were reported from the USA, where annual costs resulting from chronic lower back pain patients were estimated at almost $12,000 for medical care alone, with a large proportion coming from in- and outpatient service [6]. The problem of back pain may even increase in future, since members of the western population are showing a decrease in physical activity and an increase in weight over the years (e.g., [7]).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 255 abstracts, based on the inclusion criteria, 56 were selected for further review in full text. In the past 11 years, 55 publications examined economic outcomes associated with pregabalin in FM or neuropathic pain . These 55 publications presented results from 53 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Our review identified 28 primary studies examining per‐patient costs associated with pregabalin for neuropathic pain and FM. Most studies were retrospective analyses reporting direct costs only, and most were conducted in the US, with 2 from Spain and 1 from Sweden . In the US, patients receiving pregabalin for FM had a similar or higher amount of healthcare use following treatment initiation compared with standard therapies .…”
Section: Resultsmentioning
confidence: 99%